Inhibition of Sirt2 Alleviates Fibroblasts Activation and Pulmonary Fibrosis via Smad2/3 Pathway - Gong, Hui; Zheng, Chenyi; Lyu, Xing; Dong, Lini; Tan, Shengyu; Zhang, Xiangyu (Frontiers in Pharmacology, 2021)
Idiopathic pulmonary fibrosis (IPF) is a fatal disease with unknown cause and limited treatment options. Its mechanism needs to be further explored. Sirtuin2 (Sirt2), a nicotinamide adenine dinucleotide (NAD)-dependent deacetylase, has been proved to be involved in the fibrosis and inflammation in the liver, kidney and heart. In this study, we aimed to evaluate the role of Sirt2 in pulmonary fibrosis. We found that Sirt2 expression was upregulated in transforming growth factor-β1 (TGF-β1) treated human embryonic lung fibroblasts. Sirt2 inhibitor AGK2 or the knockdown of Sirt2 expression by targeting small interfering RNA (siRNA) suppressed the fibrogenic gene α-SMA and Fibronectin expression in TGF-β1 treated fibroblasts and primary lung fibroblasts derived from patients with IPF. In addition, Sirt2 inhibition suppresses the phosphorylation of Smad2/3. Co-immunoprecipitation showed that there is interaction between Sirt2 and Smad3 in the TGF-β1 treated lung fibroblasts. In bleomycin-induced pulmonary fibrosis in mice, AGK2 treatment significantly mitigated the degree of fibrosis and decreased the phosphorylation of Smad2/3. These data suggest that Sirt2 may participate in the development of IPF via regulating the Smad2/3 pathway. Inhibition of Sirt2 would provide a novel therapeutic strategy for this disease.